THE CHALLENGES AND EFFECTIVENESS OF VALUE ADDED TAX RATES AS A DISTRIBUTIONAL TOOL (EU and comparative law issues and challenges series (ECLIC), 2018)
In modern states, taxation of consumption, with taxation of personal and corporate income, is the most aboundant tax source. As a rule, developing countries such as the Republic of Croatia are mostly turning to taxation of consumption through the general sales tax of goods and services and special taxes, ie excise duties. Until 1 January 1998, consumption in the Republic of Croatia was taxed by the application of sales tax on products and services. The rates were proportional and applied to the selling price. Product and service tax disadvantages were attributable to its cumulative effect, which means that the tax burden was greater when the production process was realized in several phases. Value added tax (VAT) was introduced due to the need to reform the entire Croatian tax system in new economic and political circumstances and the need to harmonize the Croatian tax system with the EU tax system. The extraordinary place and role of this tax was reflected not only in its pronounced financial leverage in relation to other taxes, but also in frequent use as an instrument for regulating supply and demand for certain products. VAT is the net surplus sales tax that is calculated at each stage of the production and sales cycle, but only on the value added that was created at that stage, not on the total production value. Of great importance is the type of rate that applies when it comes to VAT. In the Republic of Croatia there is a fairly high proportional rate which has an adverse regressive effect on a wide circle of taxpayers. In this paper, the authors will discuss and try to analyze the efficiency of VAT rates and how to reduce the regressive effects of VAT through various measures of a positivelegal tax system in the Republic of Croatia. We consider it important to note that the framework of this paper does not allow a detailed analysis and that we are forced to limit ourselves exclusively to some aspects of the issue at hand.